Culture and Consumer Ethics - Swaidan, Ziad (2012)
Disparity in consumer ethics reflects cultural variations; these are differences in the collective programming of the mind that distinguishes one culture from another. This study explores the differences in consumer ethics across cultural dimensions using Hofstede’s (in Culture’s consequences: international differences in work-related values, Sage, Beverly Hills, 1980) model (collectivism, masculinity, power distance, and uncertainty avoidance) and Muncy and Vitell (in J Bus Res 24(4):297–311, 1992) consumer ethics model (i.e., illegal, active, passive, and no harm). This is the first study to empirically explore consumer ethics using these two major constructs. Seven hundred sixty one African American consumers were used to test the four major hypotheses developed in this study. Current research has revealed that there are significant differences in ethics between consumers who score high and consumers who score low on Hofstede’s four cultural dimensions. In general, this research revealed that consumers who score high on collectivism, high on uncertainty avoidance, low on masculinity, and low on power distance scales reject questionable activities more than consumers who score low on collectivism, low on uncertainty avoidance, high on masculinity, and high on power distance. This study should prove valuable to international marketers because the Hofstede cultural model allows managers to identify differences in consumer ethics across different cultures and thus provides a theoretical base for designing effective marketing strategies.
Keywords: Muncy and Vitell model; African American subculture; Consumer ethics; Hofstede model; Culture